PENGARUH MASSA RAGI SACCHAROMYCES CEREVISIAE TERHADAP KADAR BIOETANOL BERBAHAN DASAR LIMBAH KULIT KOPI ARABICA (COFFEA ARABICA L.) - Febrina, Resa Vernia; Nasution, Reni Silvia (AMINA, 2020)
Arabica coffee skin waste contained 49% cellulose, 24,5% hemicellulose, and 7,63% lignin that can be used to produce bioethanol. The purpose was to know the effect of the various mass of yeast Saccharomyces cerevisiae (3, 9, and 15 gram). The method used consists of several steps such as pretreatment, hydrolysis, fermentation using Saccharomyces cerevisiae, distillation process, and determining bioethanol content using chromatography gas. The bioethanol content from 25 gram arabica coffee skin waste with 3, 9, and 15 gram yeast for 3 days fermentation was 0,35%; 0,57%; and 1,46%. The highest bioethanol content was 1,46% found by adding 15 gram yeast Saccharomyces cerevisiae for 3 days fermentation.